The timing of conflict violence: Hydraulic behavior in the Ugandan civil war. (September 2015) - Carter, Timothy Allen; Veale, Daniel Jay
Researchers generally examine how variables directly affect events in war. Some variables, however, may not simply increase or decrease conflict events but may instead displace them. In wartime, this dynamic may result from the conditional decision-making made by militaries constrained, at least partially, by time. When there is a necessary regularity to military operations, decision-making may be complicated by factors such as inclement weather, and this regularized pressure to act may produce a hydraulic relationship between inclement weather and events. In this dynamic, today's inclement weather, such as rain, may displace today's events. Conversely, yesterday's rain may increase today's, with planned events postponed. Similarly, tomorrow's rain may also increase today's events, with planned activities moved forward. We test this hydraulic argument with geo-referenced data from the recent Ugandan civil war and find significant evidence that conflict events are fluid in time. Inclement weather constrains and also displaces events.